Convergence of Homotopy Perturbation Method for Solving Integral Equations: Hossein Jafari, M. Alipour, H. Tajadodi - Team, Support (Thai Journal of Mathematics, 2010)
The aim of this paper is convergence study of homotopy perturbation method (HPM) for solving integral equations in general case. The homotopy perturbation method is a powerful device for solving a wide variety of problems. Using the homotopy perturbation method, it is possible to find the exact solution or an approximate solution of the problem. Some illustrative examples are presented.